Influência do risco de queda sobre a marcha com obstáculos em idosos - Ceccon, Fernando Gomes (2017)
The older population is growing considerably in recent years. It motivates studies on aging to help to understand its mechanisms and effects on mobility and risk of fall in older adults. A fall is considered the sixth more frequent cause of death among older adults. The Timed Up & Go test (TUG) is used to assess the risk of fall. However, TUG considers a condition of gait without any challenge. In this study we investigate whether risk of fall identified by TUG influence performance of gait with obstacles in older adults. Thirty older women were organized in two groups, a group with risk of fall (n=15) and other group without risk of fall (n=15) as determined by TUG. We evaluated the gait kinematics during obstacle crossing considering obstacles of different heights. We observed that although TUG discriminates the older adults regarding risk of fall, foot clearances during obstacle crossing did not differ among the groups. One plausible explanation for these results can be the fact that TUG does not involve obstacle crossing, which is a task with high neuromuscular and cognitive demands to the older adults. It was evident that older adults with or without risk of fall detected by TUG do not differ regarding obstacle crossing.